Anteaglonium saxicola (Anteagloniaceae, Pleosporales), a new species isolated from rocks in northern Thailand - Suwannarach, Nakarin; Kumla, Jaturong; Khuna, Surapong; Thitla, Tanapol; Senwanna, Chanokned; Hongsanan, Sinang; Lumyong, Saisamorn (Phytotaxa, 2023)
A new species of rock-inhabiting fungi, described herein as Anteaglonium saxicola, was isolated from rock samples collected from natural forests in Lamphun Province, Thailand. This species was introduced based on morphological characteristics and multi-gene phylogenetic analyses. Multi-gene phylogenetic analyses based on a combination of the 28S large subunit (nrLSU), 18S small subunit (nrSSU), and internal transcribed spacer (ITS) of the nuclear ribosomal DNA (rDNA) along with the translation elongation factor (tef1-α) genes revealed that A. saxicola belongs to the clade of the genus Anteaglonium and is clearly distinct from other known Anteaglonium species. This paper provides a description, illustrations, and phylogenetic position of this novel species.